2012
DOI: 10.1186/1471-2377-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Masitinib treatment in patients with progressive multiple sclerosis: a randomized pilot study

Abstract: BackgroundTreatment options for patients suffering from progressive forms of multiple sclerosis (MS) remain inadequate. Mast cells actively participate in the pathogenesis of MS, in part because they release large amounts of various mediators that sustain the inflammatory network. Masitinib, a selective oral tyrosine kinase inhibitor, effectively inhibits the survival, migration and activity of mast cells. This exploratory study assessed the safety and clinical benefit of masitinib in the treatment of primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 32 publications
1
78
0
Order By: Relevance
“…Imatinib, a potent PDGFR inhibitor, rarely causes HFSR [61]. Masitinib, also an inhibitor of PDGFR, has a low incidence of HFSR [25]. Moreover, PDGFR and KIT are localized in the ductal epithelium of eccrine sweat glands, providing an additional explanation for its palmar-plantar distribution [62,63].…”
Section: Pathogenesismentioning
confidence: 97%
See 2 more Smart Citations
“…Imatinib, a potent PDGFR inhibitor, rarely causes HFSR [61]. Masitinib, also an inhibitor of PDGFR, has a low incidence of HFSR [25]. Moreover, PDGFR and KIT are localized in the ductal epithelium of eccrine sweat glands, providing an additional explanation for its palmar-plantar distribution [62,63].…”
Section: Pathogenesismentioning
confidence: 97%
“…Indications for kinase inhibitors have recently expanded beyond malignancies to various autoimmune diseases, such as rheumatoid arthritis, psoriasis, inflammatory bowel disease, asthma, and multiple sclerosis [25,26]. Therefore, it is likely that we will encounter the development of many more MKIs to suppress immune cells in years to come.…”
Section: Multikinase Inhibitors (Mkis)mentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, clinical trials have shown therapeutic effects of masitinib in cases of mastocytosis, a rare disease characterized by abnormal accumulation and activation of mast cells in various tissues and organs (28). Masitinib was also shown to beneficially modulate CNS function in multiple sclerosis (29), stroke (30), and Alzheimer' s disease (31). In addition, a recent phase III clinical trial with masitinib in ALS has shown promising therapeutic effects in a significant group of patients, slowing the deterioration of motor functions and reducing the decline in quality of life (32).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that mast cells actively play a role in pathogenesis of MS by releasing vasoactive mediators that sustain inflammatory cascade, disrupting the BBB, and stimulating activated T cells, amongst other mechanisms [93,94]. In a phase IIa proof-of-concept trial, masitinib was, overall, well tolerated and found to have positive but not statistically significant effect on clinical progression in patients with progressive MS [95]. A phase IIb/III study of masitinib in patients with relapse-free SPMS or PPMS is in progress (NCT01433497).…”
Section: Masitinibmentioning
confidence: 99%